Al-Takrar Fii Daw'i Al-Dirasat Al-Uslubiyah Al-Haditsah - Aiyub Berdan (An-Nahdah Al-'Arabiyah)
The phenomenon of repetition is an expressive device used by poets and writers to generate meaning and create rhythm, which is central to the poetic nature of their works. This rhythm is built through repetition, whether by repeating one or more patterns within a stanza or throughout the poem. This study examines repetition from a modern stylistic perspective. The research question is: what is the relationship between repetition and stylistic studies in light of modern stylistics? The objective is to uncover how repetition relates to stylistic studies within this modern context. The research employs a descriptive-analytical method. Conclusions include: 1. Repetition is closely related to stylistic studies because style depends on the frequency of repeated linguistic elements (phonological, grammatical, and lexical). 2. Stylistic studies extend beyond the observation of phonological, lexical, and grammatical elements to various levels of analysis.